Corporate Social Responsibility in Europe and the U.S.: Insights from Businesses’ Self-presentations - Maignan, Isabelle; Ralston, David A. (Journal of International Business Studies, 2002)
The paper compares the extent and content of businesses’ communications about corporate social responsibility (CSR) in France, the Netherlands, the U.K., and the U.S. In particular, the study investigates the nature of CSR principles, processes, and stakeholder issues discussed in web pages. The results show that businesses in the four countries do not display the same eagerness to appear as socially responsible and employ diverse means to convey social responsibility images.